Mediating effect of ethical climate between organizational virtuousness and job satisfaction - Humaira Asad; Rabia Naseem; Rafia Faiz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The purpose of this study is to examine the relationship between organizational virtuousness and job satisfaction with a mediating role of ethical climate. The study follows an explanatory research design. We hypothesized that increase in the perceived virtuousness in the presence of an improved ethical climate will lead to a greater job satisfaction. This hypothesized relationship is tested using data from 271 faculty members working with four universities in Pakistan. To collect the data, a questionnaire was developed using recognized scales. The internal consistency of the scale is checked through Cronbach's alpha. The data analysis was done using Pearson correlation coefficients and mediation analysis. Mediation analysis is done by applying PROCESS (Hayes, 2012). The results show that ethical climate partially mediates the effect of organizational virtuousness on job satisfaction. This paper advances suggestions to the upper management in the education sector that how organizational virtuousness and ethical climate can increase the job satisfaction among academicians. When the employees experience compassion, love and forgiveness, they may have a stronger tendency to own the organization and the satisfaction with their jobs increases. The findings of this study have practical as well as policy implications. In addition, the empirical evidence provided in this study may open the future avenues of research in this domain. This paper has two major contributions. First, it introduces ethical climate as the mediator between organizational virtuousness on job satisfaction. Secondly, it provides a robust empirical analysis by using a relatively more sophisticated macro called PROCESS by Hayes (2012).
Keywords: 330; Organizational virtuousness; ethical climate; job satisfaction; PROCESS